Multi-dimensional effects on Cladoceran (Crustacea, Anomopoda) assemblages in two cascade reservoirs in Southeast Brazil - Perbiche-Neves, Gilmar [UNESP]; Nogueira, Marcos Gomes [UNESP] (Wiley, 2010)
The Cladocera assemblages in two cascade reservoirs located in the Paranapanema River in Brazil were studied during two consecutive years. Upstream Chavantes Reservoir is an accumulation system, with a long water retention time, high depth and oligo-mesotrophic status. The downstream Salto Grande Reservoir is a small, run-of-river reservoir, with a short water retention time, shallow depth and meso-eutrophic status. The goal of this study was to determine the inter- and intra-reservoir limnological differences with emphasis on the Cladocerans assemblages. The following questions were posed: (i) what are the seasonal dynamics of the reservoir spatial structures; (ii) how dynamics, seasonally, is the reservoirs spatial structure; and (iii) are the reservoir independent systems? A total of 43 Cladoceran species were identified in this study. Ceriodaphnia silvestrii was the most abundant and frequent species found in Chavantes Reservoir, while C. cornuta was most abundant and frequent in Salto Grande Reservoir. The Cladoceran species richness differed significantly among sampling sites for both reservoirs. In terms of abundance, there was a significant variation among sampling sites and periods for both reservoirs. A cluster analysis indicated a higher similarity among the deeper compartments, and the intermediate river-reservoir zones was grouped with the riverine sampling sites. For the smaller Salto Grande Reservoir, the entrance of a middle size tributary causes major changes in the system. A distinct environment was observed in the river mouth zone of another small tributary, representing a shallow environment with aquatic macrophyte stands. A canonical correlation analysis between environmental variables and Cladoceran abundance explained 75% of the data variability, and a complementary factorial analysis explained 65% of the variability. The spatial compartmentalization of the reservoirs, as well as the particular characteristics of the two study reservoirs, directly influenced the structure of the Cladoceran assemblages. The conditions of the lacustrine (dam) zone of the larger Chavantes Reservoir were reflected in the upstream zone of the smaller downstream Salto Grande Reservoir, highlighting the importance of plankton exportation in reservoir cascade systems. The comparative spatial-temporal analysis indicated conspicuous differences between the two reservoirs, reinforcing the necessity of considering tropical/subtropical reservoirs as complex, multi-compartmental water systems. © 2010 The Authors. Journal compilation © 2010 Blackwell Publishing Asia Pty Ltd.
Keywords: Limnological variables; Retention time; Trophic conditions; Tropics; Zooplankton; abundance; canonical analysis; crustacean; limnology; reservoir; retention; species richness; trophic conditions; zooplankton; Brazil; Paranapanema River; Anomopoda; Ceriodaphnia; Ceriodaphnia cornuta; Cladocera; Crustacea